Pengaruh Citra Merek Terhadap Keputusan Pembelian KFC Ramayana Dengan Kepercayaan Merek SebagaiVariabel Intervening : Studi Kasus Pada Pelanggan KFC Ramayana Di Kota Tebing Tinggi - Rahayu, Kiki; Sarwoto (Economic Development Progress, 2023)
This study aims to determine "the influence of brand image on purchasing decisions with brand trust as an intervening variable (T-shirt Study on KFC Ramayana Customers in Tebing Tinggi City)". The type of research used in this research is explanatory research. The population in this study were all consumers who had consumed KFC Ramayanan in Tebing Tinggi City. In determining the sample used the Slovin formula. Sampling using non-probability sampling technique. Samples were taken as many as 90 respondents. The analysis tool in this study uses the help of the SEM analysis program with Smart PLS 3.0 software. Based on the results of the study showed that: 1). Brand Image (X) has an effect on Brand Trust (Z), 2). Brand Image Variable (X) has an effect on Purchase Decision (Y), 3). Brand Trust Variable (Z) has an effect on Purchase Decision (Y), 4). Brand Image Variable (X) has an effect on Purchase Decision (Y) with Brand Trust (Z) as Intervening Variable.